Deterioration of groundwater quality in the vicinity of an active open-tipping site in West Malaysia - ., Bahaa-eldin EA Rahim, I Yusoff, AR Samsudin, WZW Yaacob, AGM Raf (2010)
There is an urgent need for characterization of leachate arising from waste disposal to ensure a corresponding effective leachate management policy. Field and laboratory studies have been carried out to investigate the impact of municipal landfill leachate on the underlying groundwater at a site in West Malaysia. The solid waste was disposed of directly onto an unprotected natural soil formation. This situation was made worse by the shallow water table.